Investigation on hela cells behaviour induced with pulse electric field for wound healing application - Milad Zaltum, Mohamed Ahmed (2017)
This study focuses on the investigation of pulsed electric field (PEF) exposure effect on HeLa cells (cervical cancer cells) for in-vitro experiments. The study focused mainly on real time experimental setup for cell morphological properties imaging. In the experimental setup, a modified EC magnetic chamber with incubator system is used to maintain the real time in-vitro environment for exposing the HeLa cells to high electric field. A Nikon inverted microscope (Ti-series) with Metamorph® time lapse application is utlized for image capturing and video recording. The first investigation is to look at the proliferation rate of HeLa cells within 72 hours inside the modified chamber. This first investigation is utmost important to see if there is any effect from the PEF exposure. From this, it was found that the HeLa cell growth rate increased up to 50% faster when applied Electroporation (EP) in comparison to the cell without EP treatment. The investigation was continued to look at the best PEF parameter that assisted in the growth rate of HeLa cells. These investegations motivates the need of finding the best parameters for PEF exposure that are suitable for HeLa cell reversible condition. This study continues to look at the relation between amplitude and duration of PEF effect on the HeLa cell growth rate. The cells were subjected to single pulse, constant field strength of lkV/cm and pulse durations ranging from 30µs to 600µs. It was found that at l00µs pulse duration the HeLa cell growth rate increased dramatically and achieving confluency faster in comparison to the cells exposed with other pulse durations. After obtaining the best parameter for HeLa cell (lkV/cm, l00µs, & single pulse) the potential application of the EP technique for wound healing was explored. The result of the exposed cells to PEF revealed a five times faster healing rate than control group. Additionally, we have used Microcontact printing (MCP) technique for cell guidance and assembling. The results indicates that the cells aligned and elongated more on fibronectin pattern substrate under PEF than without PEF. Thus, PEF usage on biological cells would enable a novel method for assisting drug free wound repair systems and many other potential biomedical engineering applications.